Over-Dentures and Attachments: A Review of Literature - Rasmita Kumari Samantaray1 , Krishna Nanda1 , Debashish Sahoo1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Tooth-retained overdentures are a simple and cost-effective treatment than the implant-supportedoverdentures. When few teeth are present which are periodontally strong can be used as abutments foroverdenture fabrication. This helps in the retention and stability of the final prosthesis. The extraction ofteeth results in bone resorption, so preserving them as an abutment can not only provide retention andstability to the denture but also prevents bone loss and provide proprioception. Above all, “it gives thepatient the satisfaction of having prosthesis with his natural teeth still present”